Shari’ah governance practices in credit cooperatives in Malaysia - Hassan R.; Samad R.R.; Shafii Z. (International Islamic University Malaysia, 2024)
Cooperative sector governance is instrumental in ensuring the effectiveness, responsibility, and accountability in both conventional and Shari’ah-compliant cooperatives. This study examines Shari’ah governance (SG) arrangements within the cooperatives in Malaysia. The objectives of this paper are to explore the application of SG in the cooperative sector in Malaysia and to evaluate the adequacy of SG adoption in cooperative. This study uses qualitative methods where the data are collected using focus group discussions and in-depth interviews with regulators, experts, and the governance organs of the cooperatives. The study focuses on credit cooperatives that have been listed in the 100 Best Cooperative Directory issued by Suruhanjaya Koperasi Malaysia (SKM) annually from 2012 to 2016. The findings from thematic analysis on interviews conducted indicate that the first objective, most respondents agreed that cooperatives should be operated based on the objectives of its establishment. The findings on the adequacy of adoption of SG in Shari’ah-compliant cooperatives indicate that the practice is at an infancy stage, with plenty of support and motivation are needed to ensure effective and efficient implementation of SG. Emergent findings from the interviews reveal that the Islamic attributes are crucial for a cooperative’s SG organs such as Islamic accountability, Shari’ah mindset, Islamic culture, awareness and readiness, manpower competencies and cooperation (ta'awun). It is vital for the SG organs to have such attributes in order to foster awareness among them to be more responsible and willing to adopt good SG practices. The observation of good SG practices in the cooperative sector in Malaysia can help the cooperative movement to positively grow and contribute equitably to community.